Determinan Praktik Transfer Pricing dengan Firm Size Sebagai Pemoderasi Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Lina Maulida; Agus Wahyudin (Jurnal Akuntansi Bisnis, 2020)
The purpose of this study is to analyze the effect of debt covenant, tax minimization, and audit quality on transfer pricing practice with firm size as the moderating variable. Employing purposive sampling, as much as 21 mining companies listed on the IDX in 2017-2019 were available for the test of hypothesis . Moderated regression analysis was used for the test of hypothesis. The results showed that debt covenants have no significant effect on transfer pricing. Tax minimization and audit quality have negative effect on transfer pricing and audit quality. In addition, firm size does not significantly moderate the relationship between debt covenant and transfer pricing, but firm size can significantly moderate the relationship between tax minimization and transfer pricing and can also significantly moderate the relationship between audit quality and transfer pricing.